Implementasi Pendidikan Al-Qur’an pada Anak Berkebutuhan Khusus - Abdul Rouf (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2021)
Children with special needs have different features, some are easier to catch and remember during learning, including learning the Qur'an and some have to be repeated for several weeks before they can remember. This study aims to determine the implementation of al-Qur’an education for children with special needs. This study aims is qualitative in nature, taking the background of the Pelangiku Inclusion Elementary School, Kepanjen Jombang. Data collection is done by means of observation, interviews or interviews, and documentation. While the data analysis is inductive, that is, an analysis based on the data obtained is then developed in certain relationships or becomes a hypothesis. The results showed that al-Qur’an Education for Children with Special Needs at Pelangiku Inclusion Elementary School Kepanjen Jombang was applied using the Kindergarten Recitation method. Because with this method the child is easier to understand and remember. For their habituation, every day they are introduced to reading prayers before and after studying, reading asthma'ul husna, reading short letters, reading simple prayers of daily activities such as prayers after and before bed, prayer 'a goes in and out of the bathroom, prayer travels.